Elucidating the binding affinity of meso porphyrin derivatives with Bcl-2 through synthesis and molecular docking analysis - Yasothaa Ramaiyah; Mohd Bakri Bakar; Muntaz Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2023)
Reversing multi-drug resistance in a clinical setting remains a formidable issue to date. Porphyrin has high efficiency to conjugate with chemotherapy drugs and effectively deliver within the nucleus of cancer cells which helps in lowering side effect to normal cells. As compared to naturally occurring beta-substituted porphyrins, synthetic meso-substituted porphyrins have numerous benefits. An extensive variety of substituents have been developed with porphyrins. There are eight new porphyrin derivatives synthesised in this research compounds 14-21 which differ from one size to another using Sonogashira and Suzuki coupling techniques. Sonogashira coupling method undergoes a reaction between alkyne terminal sp hybridized carbon and vinyl halide’s sp2 carbon in the presence of a Palladium catalyst. Furthermore, Suzuki coupling method has been an effective method in conjugation of aryl halides and borylated porphyrins. The synthesized new compounds were characterized by ultra-violet spectroscopy (UV-Vis), high resolution mass spectrometer (HRMS) and nuclear magnetic resonance (NMR) to confirm successful formation of all new compounds. The docking analysis was performed for compound 14-21. Compounds 16 and 18 showed the greater binding mode at the Bcl-2 protein pocket regards free or metal substituted porphyrin with longer linker chain and less bulky compared to compounds 17 and 19. This study could discover the structure of porphyrin that affects accumulation in cancer cells that potentially transmissible to target tumour.